An empirical evaluation of the effect of Covid-19 travel restrictions on Canadians' cross border travel and Canadian retailers - Jen Baggs; Loretta Fung; Beverly J. Lapham (Queen's University, Department of Economics, 2021)
This paper estimates the impact on Canadian retailers' revenues of significantly decreased international travel by Canadians in response to the Covid-19 related travel restrictions imposed on the US-Canada border. We use detailed data from 1991 to 2020 on Canadians' travel to the United States to estimate the monthly fraction of a community's residents who cross the border for 237 communities within 150 kilometres of the border. We estimate the model of cross-border travel from Baggs, Fung and Lapham (2018) and use those estimates to establish community-level counterfactual crossing rates had the pandemic not occurred. We then combine those rates with actual crossing rates to estimate the revenue losses that small Canadian retailers' avoided due to the near cessation of cross-border travel by Canadians as a result of the pandemic. Our results suggest that, on average, the border closure prevented a 1.7% decrease in revenues for a small Canadian retailer located within 150 kilometers of the border. However, we document considerable variation in the magnitude of this decrease across communities and retail sectors, with estimates ranging from approximately 0% to 234%. Specifically, retailers that are located in less affluent communities near sizeable US shopping opportunities and that are in sub-sectors that cater to travelers experienced the largest foregone revenue losses due to border closures in 2020.
Keywords: F1; 330; Covid-19; cross border shopping; international price differences